Density and de-nitrifying potential of indigenous bacterial assemblage in mangrove and seagrass in the North of Vietnam - Le Thanh, Huyen; Dao Thi , Anh Tuyet; Le Minh, Hiep; Nguyen Tien, Dat; Ha Thi , Binh; Do Trung , Sy; Do Manh, Hao (Vietnam Journal of Marine Science and Technology, 2021)
This study assessed the density and de-nitrification potential of indigenous microorganisms in mangroves and seagrass beds in northern Vietnam through two mangrove ecosystems in Tien Yen - Quang Ninh and Bang La - Hai Phong and three seagrass beds in Ha Coi and Dam Ha - Quang Ninh and Tam Giang - Thua Thien Hue. The analysis results of 4 sampling times in rainy and dry seasons during 2017–2019 showed that the density of de-nitrifying bacteria ranged from (1.0 × 102)–(4.6 × 103) MPN/mL, averaging 1.1 ± 0.3 × 103 MPN/mL. The density in mangroves was higher than that in seagrass (a = 0.05). De-nitrification rates ranged from 0.0 µgN/wet to 69.0 µgN/wet soil g/hour, averaging 18.4 ± 7.4 µgN/wet soil g/hour. The rate at the experiments added 0.5 mgN/L in seagrass was higher than that in the mangrove. The density and rate of de-nitrification were significantly correlated with many environmental factors, especially density of sulfur-oxidizing bacteria, the density of nitrifying bacteria, pH, Eh, Nts, N-NH4, P- PO4 and BOD5.